2015
DOI: 10.1111/jgh.12780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low‐dose proton pump inhibitor on preventing upper gastrointestinal bleeding in chronic kidney disease patients receiving aspirin

Abstract: Prophylactic low-dose PPI can reduce the risk of non-variceal UGIB in dialysis patients receiving aspirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In addition, HD patients usually have several comorbidities, such as ischemic heart disease, cerebral infarction, and peripheral arterial disease, and these diseases result in a high prevalence of ESRD patients taking antiplatelet drugs [ 24 ]. As a result, PPIs are administered to ESRD patients prophylactically to prevent gastrointestinal bleeding [ 25 ]. According to data from the Dialysis Outcomes and Practice Patterns Study (DOPPS), the proportion of patients prescribed either a PPI or an H2 receptor antagonist was 36–38%, with a concomitant increase in the use of PPIs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HD patients usually have several comorbidities, such as ischemic heart disease, cerebral infarction, and peripheral arterial disease, and these diseases result in a high prevalence of ESRD patients taking antiplatelet drugs [ 24 ]. As a result, PPIs are administered to ESRD patients prophylactically to prevent gastrointestinal bleeding [ 25 ]. According to data from the Dialysis Outcomes and Practice Patterns Study (DOPPS), the proportion of patients prescribed either a PPI or an H2 receptor antagonist was 36–38%, with a concomitant increase in the use of PPIs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyun Lim et al studied the use of half the standard PPI dose to prevent upper GI bleeding in patients with chronic renal failure undergoing dialysis. The results showed that the incidence and risk of upper GI bleeding were significantly reduced in the prevention group compared to the nonprevention group (5.4% vs. 1.4%) [ 6 ]. This study to some extent indicated that half the conventional dose of PPI could still effectively prevent upper gastrointestinal bleeding, which was consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is presumed that reducing the dose of PPIs may reduce the adverse effects of long-term use of PPIs. Ally MR et al found that giving half of the normal dose of PPIs to patients with chronic renal disease effectively prevented GI bleeding [ 6 ]. Based on the above research, we studied the optimal degree of PPI dose reduction, which can not only effectively prevent NSAIDs-related GI bleeding but also reduce the adverse reactions of long-term use of PPIs.…”
Section: Introductionmentioning
confidence: 99%